Archaeological heritage management of the Prehistoric Art Museum of Mação, Portugal - Oosterbeek, Luiz (2020)
The current article aims to explore the management of archaeological resources in the valleys of Tejo and Ocreza rivers, Portugal, based on research, communication, and education experiences developed at Tejo Valley Prehistoric and Sacred Art Museum, Mação County, Portugal. The article gives temporal emphasis on recent years, in the 21st century, when the museum was given this name and fully restructured. First, it addresses the strategies and theoretical guidelines adopted to run the museum. Subsequently, it describes research, post-graduate studies, communication, and other educational experiences. Finally, it performs an overall assessment and suggests future paths for the management of heritage assets, mainly in museological institutions.